Developing an Organization’s Corporate Knowledge Through Action-based Learning Technologies - T. V. Aleksandrova; V. L. Popov (Управленческие науки)
The paper explores the impact of learning technologies on the development of the corporate knowledge base of modern organizations. The authors consider the action training technologies as an alternative to traditional training, which is based on the active involvement of enterprise employees in the process of generating and practical use of new corporate knowledge. A conceptual model of action training has been developed that is tested in large industrial enterprises participating in the national project “Productivity and Employment Support” in the Perm region. The study uses the methodology of system analysis, analysis methods of statistical information and expert data. There has been concluded the usage of the developed model of training by action in projects to increase productivity in industrial enterprises leads to the formation of positive effects. The practical application of the study results will allow a more reasonable definition of the implementation of training technologies for individual enterprises; will facilitate faster and more effective implementation of national programs and projects of the Russian Federation.